THE INFLUENCE THE HABIT OF READING ASMAUL HUSNA ON THE SPIRITUAL INTELLIGENCE OF STUDENTS AT DARUL HASAN INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL PADANGSIDIMPUAN - Ummi Hanipah Nasution Ummi Hanipah Nasution; Darliana Sormin; Jumaita Nopriani Lubis (RADJA PUBLIKA, 2026)
This study aims to analyze the extent of the influence of the habit of reading Asmaul Husna on the spiritual intelligence of students at SMP Islam Terpadu Darul Hasan Padangsidimpuan. The research uses a quantitative approach with a simple linear regression method on 34 students as research samples. Data were collected through questionnaires and analyzed using normality tests, linearity tests, regression, and t-tests with the assistance of SPSS. The results of the study show an R Square value of 0.449, which means that the habit of reading Asmaul Husna affects 44.9% of students' spiritual intelligence. The t-test results show a significance value of 0.000 < 0.05, so it can be concluded that the habit of reading Asmaul Husna has a positive and significant effect on students' spiritual intelligence. Therefore, the habit of reading Asmaul Husna is effectively used as a strategy for developing spiritual intelligence and religious character in integrated Islamic school.